2014
DOI: 10.1021/cm5027305
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Hybrid Organogels Based on Miniemulsion Synthesis of Morphologically Complex Polymer/Surfactant/Calcium Phosphate Nanostructures

Abstract: Morphologically complex amorphous calcium phosphate nanostructures are synthesized within supersaturated water-in-oil miniemulsions stabilized by a mixture of a calcium bis­(2-ethylhexyl)­phosphate (Ca­(DEHP)2) surfactant and poly­(ethylene oxide)19-poly­(propylene oxide)69-poly­(ethylene oxide)19 (P123) triblock copolymer. Solvent evaporation at room temperature results in self-supporting viscous organogels comprising an interconnected network of calcium phosphate nanofilaments embedded within a continuous po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Moreover, the large particles, approximately 90-110 nm diameters, which presumably from agglomeration of the small particles by themselves were observed. Referred from previous paper [7], the results showed that SDS was the main component to form water-in-oil emulsions and nanofibrous structure, whereas the addition of P123 as template could still stabilize the spherical structure. However, nanofibrous structure might be changed to the thicker network nanofibers.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Moreover, the large particles, approximately 90-110 nm diameters, which presumably from agglomeration of the small particles by themselves were observed. Referred from previous paper [7], the results showed that SDS was the main component to form water-in-oil emulsions and nanofibrous structure, whereas the addition of P123 as template could still stabilize the spherical structure. However, nanofibrous structure might be changed to the thicker network nanofibers.…”
Section: Resultsmentioning
confidence: 59%
“…Emulsion methods are known to be low-cost procedures performing under mind condition and can be used to produce small particle sizes (in nanometer to submicron) [6]. Pluronic polymer, poly (ethylene oxide)19-block-Poly (propylene oxide)69-block-poly (ethylene oxide)19 (P123), has widely used as a template to form gel, and control the size, structure and morphology of particles [7]. In this study, P123 was added in order to form a gel which could facilitate the application of the product on the exposed teeth.…”
Section: Introductionmentioning
confidence: 99%
“…β‐Tricalcium phosphate [β‐TCP, β‐Ca 3 (PO 4 ) 2 ] as a bioactive material has found wide applications in biomedicine . β‐Ca 3 (PO 4 ) 2 offers advantage of accepting wide range of cationic substitutions in its five different in‐equivalent Ca 2+ sites .…”
Section: Introductionmentioning
confidence: 99%
“…The hierarchical micro/nano-architecture constructed by nanobuilding blocks via bottom-up approaches has attracted special interest because of their unique physical and chemical properties and potential application in the fields of materials. [1][2][3][4] Presently, much attention has been devoted to develop various methods to prepare hierarchical micro/nano-architectures, including template-assisted growth, electrochemical deposition, and various solution techniques et al [5][6][7][8][9] Regretfully, these approaches mentioned above have been mostly applied to inorganic materials. Few efforts focus on the fabrication of hierarchical micro/nano-architectures of organic small molecule materials, especially energetic materials.…”
Section: Introductionmentioning
confidence: 99%